MURCIA Y EL CINE EN LA DÉCADA DE LOS AÑOS VEINTE: LA PRODUCCIÓN DE PELÍCULAS DOCUMENTALES. EL CINE-CLUB DE MURCIA. 1936 - Canovas Belchi, Joaquín T. (Imafronte, 1986)
The film production in Spain, during the nineteentwenties lacks as yet an exhaustive study, which the author of this paper is working on for his Doctor’s Dissertation. Madrid is the centre of the national cinematography, and to a lesser degree, Barcelona and Valencia. In the first of the country only documentary and short films have been produced,. in Murcia, five films have been made, but they are still unknown. 0ther motion pictures have been filmed on regional themes, at the same timer, but they are French productions, Foundation of the movieclub in Murcia in 1935. Ideological programme.